A etnografia nalgumas expedições científicas em Timor no século XIX - Schouten, Maria Johanna Christina (2018)
In the nineteenth century, diverse geological, biological and anthropological features of the Island of Timor were explored and interpreted. Those explorations were often the by-product of travels with quite different goals, such as reconnaissance voyages to Australia, research in other parts of Southeast Asia, whale-hunting, or the administrative concerns of Dutch and Portuguese civil servants. In this text, which deals in particular with ethnographic details found during expeditions in Timor, three quite different study travels are outlined: the first the French multidisciplinary expedition led by Nicolas Baudin, at the beginning of the century; the second the round trips by the Scottish naturalist Henry Forbes and his wife Anna, in the 1880s; and in the third place the digressions of the Dutch civil servant J.G.F. Riedel, during the final decades of the century. Recurring characteristics of these expeditions are the interests in the physical side of anthropology and the capacity or willingness of an explorer to adapt to customs and respect beliefs of the local population.